Measured and Perceived Conditions of Indoor Environmental Qualities (IEQ) of University Learning Environments in Semi-arid Tropics: a Field Study in Kano-Nigeria - Ali, Sani Muhammad (University of Portsmouth, 2018)
This study investigates the conditions and the levels of satisfaction with indoor environmental quality (IEQ) in naturally ventilated (NV) learning environments in Bayero University, Kano and compares the results to international comfort standards’ thresholds. It examines the thermal and visual comfort, acoustic quality as well as the indoor air quality of six learning environments in the University consisting of four lecture theatres and two laboratories. Researches in IEQ have shown that good quality indoor environment enhances occupants’ comfort, wellbeing, raises their productivity, and most importantly for this research, it raises students’ performances, reduces absenteeism, and reduces stress and fatigue among teachers. IEQ researches are mostly being undertaken in the four most advanced continents that are situated in the temperate regions of the world, but not in subSaharan Africa. Using both measurement and survey methods, internal and external physical parameters (air and radiant temperatures, air velocity, relative humidity, background noise, sound pressure level, horizontal and vertical illumination level, carbon dioxide concentration and particulate matter) were evaluated. The assessments were undertaken three times covering ten months, August 2016 to May 2017, which coincided with the three distinct seasons (warm and wet; cool and dry & hot and dry) in Kano. PMV model, as always, failed to predict the thermal conditions of the learning environments. Similarly some of the measured and calculated IEQ parameters, have not met the thresholds specified by the adaptive components of ASHRAE-55, but were in agreement with EN 15251, the respondents expressed their acceptance of their learning environments, subjectively. This is not surprising as these standards were often based on experiments implemented in developed countries, where the severity of the climatic conditions and the culture are dissimilar to sub Saharan Africa. The outcome of the research is hoped to raise awareness of IEQ potentialities among the academia, building industry professionals, building owners, university managers and other education policy makers in the region.
KerkoCite.ItemAlsoKnownAs: 2129771:26HE8V5M 2129771:26HE8V5M 5072953:LPAYJVWN 5072953:PKE3SFJF
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; evidence_review_2; openalex:n:0; ⛔ No DOI found

Education in Emergency: A Climate Change Adaptation Agendum Towards the Socio-Economic Propagation of Bangladesh - Shoeb-Ur-Rahman, Muhammad; Rahman, Muhammad Ishaq Ur; Hossain, Md. Shakib (Social Science Research Network, 2013)
Both the scientific and negotiating community has recognized Bangladesh as one of the most vulnerable countries to Climate Change effect which in future is likely to face more frequent climatic adversities. This paper emphasizes on putting the theme of ‘Education in Emergency’ in all climate change adaptation efforts in the country which can enable it to safeguard country’s important education sector during any disaster or in the recovery phase. Education has received inconsiderable amount of importance in those efforts and ultimately encompassed all the spheres of social, emotional, cognitive and physical ground which decelerate multifarious predicaments and adversities. In preparing this paper the authors highly rely on secondary sources of data. In the era of globalization, a vast number of populations remain untouched or being detracted from the light of education. It is particularly fact for country like Bangladesh where natural calamity is an incessant event due to the intrusion of globalization. Bilateral, multilateral, regional and global affiliation and association can be undertaken to the depletion of hindrances. Besides, substantial and congruous strategies, plans, policies and programs within the internal infrastructure may assist to mitigate this endanger and also comply with the commitment of education for all even in the cataclysm. For accomplishing responsiveness and flourishing prowess, an integrating approach to the management of Education in Emergency (EiE) requires coordination and collaboration among government departments or ministries and agencies, designing and upgrading courses (including issues like Need for Sustainable Development and Actions for Environment Protection, Environmental Management Tools & Environmental Assessment, Environment Pollution Management, Progress in Environmental Science, International Environment Laws etc.), as well as superior and immaculate information technology to resolve this consternation and vulnerability. Propitious and admissible approaches can ensure eco-balance and sustainable socio-economic development in a vulnerable country like Bangladesh with a proper accentuation on education in emergency. This paper will be highly helpful for policy makers both in private and public sectors to ensure sound education opportunity in the highly disaster prone i.e., coastal areas. However, this piece of effort might also cut attention of the human rights workers.
openalex: W3189963785 mag: 3189963785 KerkoCite.ItemAlsoKnownAs: 5072953:T7QBN844 5072953:TBRSF6HA
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; openalex:import; openalex:yes

Education in Emergency: A Climate Change Adaptation Agendum Towards the Socio-Economic Propagation of Bangladesh - Shoeb-Ur-Rahman, Muhammad; Rahman, Muhammad Ishaq Ur; Hossain, Md. Shakib (Social Science Research Network, 2013)
Both the scientific and negotiating community has recognized Bangladesh as one of the most vulnerable countries to Climate Change effect which in future is likely to face more frequent climatic adversities. This paper emphasizes on putting the theme of ‘Education in Emergency’ in all climate change adaptation efforts in the country which can enable it to safeguard country’s important education sector during any disaster or in the recovery phase. Education has received inconsiderable amount of importance in those efforts and ultimately encompassed all the spheres of social, emotional, cognitive and physical ground which decelerate multifarious predicaments and adversities. In preparing this paper the authors highly rely on secondary sources of data. In the era of globalization, a vast number of populations remain untouched or being detracted from the light of education. It is particularly fact for country like Bangladesh where natural calamity is an incessant event due to the intrusion of globalization. Bilateral, multilateral, regional and global affiliation and association can be undertaken to the depletion of hindrances. Besides, substantial and congruous strategies, plans, policies and programs within the internal infrastructure may assist to mitigate this endanger and also comply with the commitment of education for all even in the cataclysm. For accomplishing responsiveness and flourishing prowess, an integrating approach to the management of Education in Emergency (EiE) requires coordination and collaboration among government departments or ministries and agencies, designing and upgrading courses (including issues like Need for Sustainable Development and Actions for Environment Protection, Environmental Management Tools & Environmental Assessment, Environment Pollution Management, Progress in Environmental Science, International Environment Laws etc.), as well as superior and immaculate information technology to resolve this consternation and vulnerability. Propitious and admissible approaches can ensure eco-balance and sustainable socio-economic development in a vulnerable country like Bangladesh with a proper accentuation on education in emergency. This paper will be highly helpful for policy makers both in private and public sectors to ensure sound education opportunity in the highly disaster prone i.e., coastal areas. However, this piece of effort might also cut attention of the human rights workers.
openalex: W3189963785 mag: 3189963785 KerkoCite.ItemAlsoKnownAs: 5072953:T7QBN844 5072953:TBRSF6HA
Keywords: C:Bangladesh; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10747 Community Resilience to Natural Disasters; openalex:import; openalex:yes

The Need and Importance of Plantation in Perspective of Changing Climate of Pakistan; A Review in the Light of Islamic Teachings (Co-authored with Dr. Arshad Mahmood) - Hassan, Fikrat M.; Muhammad, . (Social Science Research Network, 2017)
Arabic Abstract:وفي إطار هذه الورقة يتضح أنه لا يمكن لأي شخص معقول أن ينكر أهمية الغابات في الحياة البشرية. الحياة لا يمكن أن يتصور دون النباتات. وللأسف، تحتل باكستان المرتبة الثالثة بين البلدان الأحد عشر التي تحدث فيها التغيرات المناخية البيئة. باسم التقدم، نحن الموهوبين إزالة الغابات بسرعة. يجب علينا زراعة غابات جديدة بحيث يمكن الحصول على العائد من الزهور والنباتات والعسل على نطاق واسع. وقد أعطى الله الرحمن الرحيم تيارات وحدائق على الدول البدائية ولكن عندما تحولوا ظهورهم من التعاليم الإلهية، استغرق الله سبحانه وتعالى يعود بركاته منهم. وتعلن الأشجار على أنها النعمة الإلهية في القرآن الكريم. أعلن النبي الكريم (P.B.U.H) المزرعة باعتبارها فائدة أبدية. ليس هذا فقط ولكن في فترة مادنيت له، وقد وضعت العديد من الأخضر حيث تم توفير العلف للخيول والجمال كما زرع الأشجار أيضا. وينبغي أن تقوم الحكومة وقسم الغابات بإذكاء الوعي بأهمية الغابات وتسهيلها في المزارع. خصوصا الأطفال يجب أن تدرس أهمية الأشجار. وينبغي الترحيب بالبحث النباتي وتشجيعه. وينبغي أن نضع في اعتبارنا أننا موجودون إذا كانت الغابات موجودة في العالم۔
openalex: W2752441632 mag: 2752441632
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:topic:T11755 Influence of Climate on Human Conflict; openalex:import; openalex:yes

Climate Change Education Curriculum for Nigeria Tertiary Education System - Dada, Abdullahi Aliyu; Muhammad, Umar (Sokoto Educational Review, 2014)
The paper attempted to propose a Climate Change Education Curriculum that is conceived to provide a clear understanding of the Climate Change phenomenon for students in Tertiary institutions in Nigeria. Nobody is left in doubt of the relevance of climate change education in Nigeria tertiary education system. Tertiary educational institutions are expected to play a proactive role in proffering solutions to climate change challenges facing Nigeria. What needs to be done is to harness resources toward putting in place a well-articulated climate change education curriculum that should provide requisite information/knowledge and skills for future leaders. Thus, it is recommended that cogent policies need to be developed to ensure that climate change education is fully integrated into tertiary education system in Nigeria; that climate change education curriculum should be offered either as a standalone specialized course or integrated within other courses; and professional development support be provided to educators so as to be able to deliver effectively and also to be able to develop relevant teaching materials on climate change that could stand the test of time.
openalex:W2967240744 mag:2967240744 KerkoCite.ItemAlsoKnownAs: 10.35386/ser.v15i2.175 5072953:PVUVRFTE
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; _z:no_pdf; oa:keyword:climate change; oa:sdg:13 Climate action; oa:topic:T10898 Factors Influencing Pro-environmental Behavior; oa:topic:T13530 Climate Change and Environmental Impact; openalex:import; openalex:n:1; openalex:yes; ⛔ No DOI found

Fatalism, Climate Resiliency Training and Farmers’ Adaptation Responses: Implications for Sustainable Rainfed-Wheat Production in Pakistan - Mahmood, Nasir; Arshad, Muhammad Umair; Kaechele, Harald; Shahzad, Muhammad Faisal; Ullah, Ayat; Mueller, Klaus (Sustainability, 2020)
Climate change is a severe threat to the agricultural sector in general and to rainfed farming in particular. The aim of this study was to investigate the factors that can potentially affect the adaptation process against climate change. This study focused on wheat farmers and farming systems in the rainfed agroecological zone of Pakistan. Farmers’ data related to climate change fatalism, the availability of climate-specific extension services, socioeconomic and institutional variables, and farm characteristics were collected. A logit model to assess farmers’ decisions to adopt an adaptation measure and a multinomial logit model to assess their choice of various adaptation measures were used. The results showed that fatalistic farmers were unlikely to implement climate change adaptation measures. The variables related to the climate-specific extension services, including farmers’ participation in training on climate-resilient crop farming and the availability of mobile communication-based advisory services, had highly significant and positive impacts on farmers’ decisions and their choice of adaptation measures. Input market access and tractor ownership also had positive and significant impacts on farmers’ decisions to adapt and their choice of adaptation measures. This study highlights the need to improve rainfed-wheat farmers’ education levels to change their fatalistic attitudes towards climate change. Furthermore, government action is needed to provide climate-specific extension services to ensure sustainable production levels that will ultimately lead to food and livelihood security under a changing climate.
openalex: W3007027287 mag: 3007027287
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:keyword:climate resiliency training; oa:topic:T10367 Agricultural Innovation and Livelihood Diversification; oa:topic:T10439 Adaptation to Climate Change in Agriculture; oa:topic:T11886 Risk Management and Vulnerability in Agriculture; openalex:import; openalex:yes

Adaptive model for thermal comfort of students in secondary schools in the tropical city of Makassar - Hamzah, Baharuddin; Mulyadi, Rosady; Ishak, Muhammad Taufik (AIP Conference Proceedings, 2022)
This research aimed to examine the thermal comfort performance of students in naturally ventilated secondary schools’ classrooms in Makassar. The analysis compared the thermal balance and the adaptive model. The study analyzed data gathered from surveys conducted at eight secondary schools and local weather stations. The data consists of the measured indoor thermal environment of 48 classrooms. The personal data, users’ perceptions, and adaptive behaviors of 1,594 students were recorded in the questionnaire sheets. The questionnaire also recorded the thermal perception of students about the thermal environments of classrooms. In terms of thermal sensation, the study found that the neutral temperature estimated by PMV was overestimated the neutral temperature developed by actual votes of students. The PMV model estimated the neutral temperature of students at 23.0 °C which was about 7 °C lower than the neutral temperature calculated using the students’ actual thermal sensation votes (30.2 °C). This was a very big discrepancy between the predicted and the actual. The adaptive thermal comfort model produces more appropriate results than the PMV model. The modified Humphrey’s model predicted more close neutral temperature to the actual one which was 29.1 °C. Students adapt to the thermal environment through several activities. This adaptation makes students remain comfortable even in the hot thermal environment.
openalex:W4313047375 mag: KerkoCite.ItemAlsoKnownAs: 2129771:FFKMCPV6 2129771:FFKMCPV6 10.1063/5.0094787 5072953:R95ZVNPF
Keywords: _C:Indonesia; _z:class:countries; _z:class:themes; _z:no_pdf; evidence_review_2; oa:keyword:thermal comfort; oa:sdg:11 Sustainable cities and communities; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T12950 Learning Environments in Education

Effects of Ceiling Fans on the Thermal Comfort of Students in Learning Environments of Bayero University, Kano, Nigeria - Ali, Sani Muhammad; D. Martinson, Brett; Al-Maiyah, Sura (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2022)
It is well known that thermal comfort is influenced by major physical parameters; air and radiant temperatures, humidity, and air speed in combination with personal attributes; clothing insulation and activity level. Although temperature is conventionally considered in adaptive thermal comfort model, as the most important physical parameter where cooling is involved, moderate air speed can enhance thermal comfort during higher temperatures. Through convective and evaporative cooling, ceiling fans cool people by causing sweat from the occupant’s body to evaporate. The northern part of Nigeria, being in the tropics, is known for higher temperature regimes for most part of the year. The use of air conditioning to achieve thermal comfort is not sustainable, for economic reasons and the lack of stable electrical energy. Therefore, a majority of naturally ventilated spaces could be kept thermally comfortable with the control of ceiling fans and operable windows. As part of a research work on learning environments in a Northern Nigerian university, this study reports on the effects of ceiling fans on the thermal comfort perception of the students in two lecture theatres. Air speed, air and radiant temperatures, relative humidity were measured, concurrently comfort surveys were undertaken in the spaces, from which activity levels and clothing insulations were obtained. Adaptive thermal comfort standards, ASHRAE 55 and EN 15251, state that thermal comfort can be maintained as air temperature rises with the use of ceiling fans operating at moderate speed. The results show that reductions of 31% and 22% in overheating from the two lecture theatres were realised, as a result of ceiling fans usage, measured by the degree hour’s exceedance indicator. These results were further corroborated by the students’ acceptance of thermal conditions of the lecture theatres at temperatures above Tmax.

An Investigation of Thermal Comfort in Classrooms in the Tropical Savanna Climate - Mustapha, Tajudeen; Hassan, Ahmad; Abdul Nasir, Muhammad; Onubi, Hilary (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2022)
Studying the thermal environment in classrooms is essential due to its impact on students' health, teaching, learning, and productivity. In the Nigerian context, there is a general lack of thermal comfort studies, and none specifically relate to secondary school settings. This study aims to investigate students' perceptions of the indoor thermal environment and to determine the optimum temperature in naturally ventilated classrooms in the tropical savanna climate. Field investigations were conducted in free-running classrooms in Abuja to evaluate occupants' thermal comfort and perceptions. The study involves 901 pupils from 21 classrooms. Data were obtained through physical measurements of thermal comfort variables and a questionnaire survey on occupants' perceptions of the indoor thermal environment. The objective assessment indicated that 86% of the classrooms were inconsistent with the ASHRAE standard–55. Although 60% of the pupils were satisfied with their thermal environment, 78% preferred a cooler than neutral temperature. The result revealed a comfort temperature of 28.9 oC. The results extend the literature on thermal comfort in classrooms to the tropical savannah climate of the west African sub-region, which has received little attention in earlier research. The findings provide foundation data for developing a comfort standard for classrooms in the zone.
KerkoCite.ItemAlsoKnownAs: 10.37934/araset.29.1.6275 2129771:BFL237GS 4874017:XFJ6HDUH
Keywords: evidence_review

A review on windcatcher for passive cooling and natural ventilation in buildings, Part 1: Indoor air quality and thermal comfort assessment - Jomehzadeh, Fatemeh; Nejat, Payam; Calautit, John Kaiser; Yusof, Mohd Badruddin Mohd; Zaki, Sheikh Ahmad; Hughes, Ben Richard; Yazid, Muhammad Noor Afiq Witri Muhammad (Renewable and Sustainable Energy Reviews, 2017)
The most prominent challenge in 21th century is global warming which seriously threats the mankind. Building sector with 40% of global energy consumption and GHG emission play a key role in this threat. In this regard, the impact of cooling systems cannot be ignored where along with ventilation and heating systems totally account for 60% of energy consumed in buildings. Passive cooling systems can be a promising alternative to reduce energy consumption. One of the oldest passive cooling system that is still being used today is windcatcher. By manipulating pressure differences and the buoyancy effect, an adequate level of ventilation in buildings can be provided by windcatchers. Since most of the previous windcatcher studies assessed the design characteristics, the current investigation focused on the indoor air quality (IAQ) and thermal comfort aspects. The review details and compares the different theoretical and experimental methods employed by researchers in different case studies to assess the IAQ and thermal comfort. It was found that most IAQ studies were conducted in the UK using CFD and experimental techniques. Previous studies assessed IAQ based on several parameters such as air flow rate, air change rate, CO2 concentration, air change effectiveness and mean age of air. The findings of the studies revealed that satisfactory IAQ were generally achieved using the windcatcher. On the other hand, thermal comfort studies of windcatchers were mainly conducted in hot climates such as in the Middle East. In addition to night ventilation, the review also looked into the different types of cooling methods incorporated with windcatchers such as evaporative cooling, earth to air heat exchangers (EAHE) and heat transfer devices (HTD). Night ventilation was found to be effective in temperate and cold conditions while additional cooling using evaporative cooling, EAHE and HTD were found to be necessary in hot climates.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.rser.2016.11.254 2129771:X5A7B6UV 4874017:QCURFWXN
Keywords: Badgir; Indoor air quality (IAQ); Natural ventilation; Passive cooling; Thermal comfort; Wind tower; Windcatcher; evidence_review

A review on windcatcher for passive cooling and natural ventilation in buildings, Part 1: Indoor air quality and thermal comfort assessment - Jomehzadeh, Fatemeh; Nejat, Payam; Calautit, John Kaiser; Yusof, Mohd Badruddin Mohd; Zaki, Sheikh Ahmad; Hughes, Ben Richard; Yazid, Muhammad Noor Afiq Witri Muhammad (Renewable and Sustainable Energy Reviews, 2017)
The most prominent challenge in 21th century is global warming which seriously threats the mankind. Building sector with 40% of global energy consumption and GHG emission play a key role in this threat. In this regard, the impact of cooling systems cannot be ignored where along with ventilation and heating systems totally account for 60% of energy consumed in buildings. Passive cooling systems can be a promising alternative to reduce energy consumption. One of the oldest passive cooling system that is still being used today is windcatcher. By manipulating pressure differences and the buoyancy effect, an adequate level of ventilation in buildings can be provided by windcatchers. Since most of the previous windcatcher studies assessed the design characteristics, the current investigation focused on the indoor air quality (IAQ) and thermal comfort aspects. The review details and compares the different theoretical and experimental methods employed by researchers in different case studies to assess the IAQ and thermal comfort. It was found that most IAQ studies were conducted in the UK using CFD and experimental techniques. Previous studies assessed IAQ based on several parameters such as air flow rate, air change rate, CO2 concentration, air change effectiveness and mean age of air. The findings of the studies revealed that satisfactory IAQ were generally achieved using the windcatcher. On the other hand, thermal comfort studies of windcatchers were mainly conducted in hot climates such as in the Middle East. In addition to night ventilation, the review also looked into the different types of cooling methods incorporated with windcatchers such as evaporative cooling, earth to air heat exchangers (EAHE) and heat transfer devices (HTD). Night ventilation was found to be effective in temperate and cold conditions while additional cooling using evaporative cooling, EAHE and HTD were found to be necessary in hot climates.
openalex: W2560795218 KerkoCite.ItemAlsoKnownAs: 10.1016/j.rser.2016.11.254 4874017:9W6ID58Z 5072953:8LUI5SFF 5072953:WV2R5MRE
Keywords: _z:class:countries; _z:class:themes; oa:keyword:indoor air quality; oa:keyword:natural ventilation; oa:sdg:7 Affordable and clean energy; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; oa:topic:T13298 Solar Chimney Systems; openalex:n:1; openalex:yes

Validation of Designbuilder Simulation Accuracy Using Field Measured Data of Indoor Air Temperature in a Classroom Building - Abba, Habu Yusuf; Majid, Roshida Abdul; Ahmed, Muhammad Hamdan; Gbenga, Olutobi (Management, 2022)
KerkoCite.ItemAlsoKnownAs: 2129771:4UHQEB9X 4682641:55AFYSVG 5072953:WM5Q6W8Y
Keywords: BE:RELEVANT; _z:class:countries; _z:class:themes; ⛔ No DOI found

An investigation of thermal comfort in classrooms in the tropical Savanna climate - Mustapha, Tajudeen Dele; Hassan, Ahmad Sanusi; Nasir, Muhammad Hafeez Abdul; Onubi, Hilary Omatule (Journal of Advanced Research in Applied Sciences and Engineering Technology, 2022)
Studying the thermal environment in classrooms is essential due to its impact on students' health, teaching, learning, and productivity. In the Nigerian context, there is a general lack of thermal comfort studies, and none specifically relate to secondary school settings. This study aims to investigate students' perceptions of the indoor thermal environment and to determine the optimum temperature in naturally ventilated classrooms in the tropical savanna climate. Field investigations were conducted in free-running classrooms in Abuja to evaluate occupants' thermal comfort and perceptions. The study involves 901 pupils from 21 classrooms. Data were obtained through physical measurements of thermal comfort variables and a questionnaire survey on occupants' perceptions of the indoor thermal environment. The objective assessment indicated that 86% of the classrooms were inconsistent with the ASHRAE standard–55. Although 60% of the pupils were satisfied with their thermal environment, 78% preferred a cooler than neutral temperature. The result revealed a comfort temperature of 28.9 oC. The results extend the literature on thermal comfort in classrooms to the tropical savannah climate of the west African sub-region, which has received little attention in earlier research. The findings provide foundation data for developing a comfort standard for classrooms in the zone.
Number: 1 openalex:W4313580688.json KerkoCite.ItemAlsoKnownAs: 2129771:SCM2XDX6 2129771:SCM2XDX6 2129771:SCM2XDX6 2129771:SCM2XDX6 10.37934/araset.29.1.6275 4874017:X7YWDRM9 5072953:FV66BCLI 5072953:KS9NTX56
Keywords: C:Nigeria; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:thermal comfort; oa:keyword:tropical savanna climate; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T12950 Learning Environments in Education; thermal sensation

A review of the applications of artificial intelligence and big data to buildings for energy-efficiency and a comfortable indoor living environment - Mehmood, Muhammad Uzair; Chun, Daye; Zeeshan; Han, Hyunjoo; Jeon, Gyuyeob; Chen, Kuan (Energy and Buildings, 2019)
After decades of evolution and improvements, Artificial Intelligence (AI) is now taking root in our daily lives, and is starting to profoundly influence the fields of architecture and sustainability. The applications of AI to sustainable architecture include energy-efficient building design, forecasting and minimizing energy consumption, strategizing for mitigating impacts on environment and climate, and enhancements in the safety and comfort of the living environment. Due to the significant increases in internet speed and accessibility and the drops in computer prices and data storage costs in recent years, Big Data (BD) nowadays plays an important supplementary role to AI. Algorithms and computer codes have been developed for data mining and analysis. BD rejuvenates AI methods and applications in many areas, including sustainable architecture. The present paper starts with an introduction to AI history and techniques. This is followed by a discussion on how AI and BD can be used to design and operate energy–efficient commercial buildings and residential houses, followed by a review of recent applications of AI and BD to energy-efficient buildings with an emphasis on the use of machine learning (ML) and large databases. Future research topics are suggested at the end of this paper. It is reemphasized in the present paper that AI, when combined with BD, can tremendously increase the energy efficiency and cost effectiveness of buildings which are designed to provide occupants with a comfortable indoor living environment.
KerkoCite.ItemAlsoKnownAs: 10.1016/j.enbuild.2019.109383 5072953:BLM2GXIE openalex: W2969536608
Keywords: Artificial intelligence; Big data; Green buildings; Sustainable architecture; _z:class:countries; _z:class:themes; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T11954 Energy Efficiency in Manufacturing and Industry Sector; oa:topic:T11963 Impact of Nighttime Light Data on Various Fields; openalex:n:1; openalex:yes

Influence of Different Roof Design Parameters on Classrooms’ Thermal Performance in Tropical Savannah Climate of Nigeria - Abba, Habu Yusuf; Bint Abdul-Majid, Roshida; Ahmed, Muhammad Hamdan; Said, El-Nafaty Abbas (Journal of Xi'an University of Architecture & Technology, 2020)
KerkoCite.ItemAlsoKnownAs: 2129771:C26A8GBA 4682641:29MGH7TW 5072953:8FCV9GGJ
Keywords: BE:LMIC; BE:RELEVANT; C:Nigeria; _z:class:countries; _z:class:themes; openalex:n:0; ⛔ No DOI found

Evaluating indoor environmental performance of laboratories in a Northern Nigerian university: 33rd PLEA International Conference - Ali, Sani Muhammad; Martinson, Brett; Al-Maiyah, Sura (Proceedings of 33rd PLEA International Conference, 2017)
Poor environmental comfort in learning spaces can have an impact on the learning capacities of students. It is not unusual to find learning spaces in Nigerian higher institutions in which the indoor environmental qualities do not meet the occupants’ requirements. Despite being in the tropics, where solar radiation is in abundance, Nigerian building industry professionals pay little attention to passive energy utilization. Knowing how buildings perform in the country may appeal to their consciousness in reconsidering this situation. This paper is part of an ongoing study on comfort in higher education facilities involving lecture theatres and laboratories in Bayero University, Kano, Nigeria. Objective and subjective assessments were undertaken during the wet-warm season of August 2016. It reports the assessment conducted on two laboratories, with a view to finding how they perform environmentally in comparison to occupants’ preferences and international comfort standards. Although some of the measured and calculated physical parameters, have not met the thresholds specified by ASHRAE-55 and EN 15251, the respondents expressed their acceptance of the laboratories’ situations subjectively. This is not surprising as these standards are often based on experiments implemented in developed countries, where the severity of the climatic conditions and the culture are dissimilar to sub Saharan Africa.
KerkoCite.ItemAlsoKnownAs: 5072953:I44GNID5 5072953:QD5TXEIW
Keywords: IEQ; Kano; Nigeria; Predicted Mean Vote; Predicted Percentage of Dissatisfied

Application of Machine Learning Techniques to Delineate Homogeneous Climate Zones in River Basins of Pakistan for Hydro-Climatic Change Impact Studies - Nusrat, Ammara; Gabriel, Hamza Farooq; Haider, Sajjad; Ahmad, Shakil; Shahid, Muhammad; Jamal, Saad Ahmed (Applied sciences, 2020)
Climatic data archives, including grid-based remote-sensing and general circulation model (GCM) data, are used to identify future climate change trends. The performances of climate models vary in regions with spatio-temporal climatic heterogeneities because of uncertainties in model equations, anthropogenic forcing or climate variability. Hence, GCMs should be selected from climatically homogeneous zones. This study presents a framework for selecting GCMs and detecting future climate change trends after regionalizing the Indus river sub-basins in three basic steps: (1) regionalization of large river basins, based on spatial climate homogeneities, for four seasons using different machine learning algorithms and daily gridded precipitation data for 1975–2004; (2) selection of GCMs in each homogeneous climate region based on performance to simulate past climate and its temporal distribution pattern; (3) detecting future precipitation change trends using projected data (2006–2099) from the selected model for two future scenarios. The comprehensive framework, subject to some limitations and assumptions, provides divisional boundaries for the climatic zones in the study area, suitable GCMs for climate change impact projections for adaptation studies and spatially mapped precipitation change trend projections for four seasons. Thus, the importance of machine learning techniques for different types of analyses and managing long-term data is highlighted.
openalex: W3090569372 mag: 3090569372
Keywords: C:Pakistan; _z:class:countries; _z:class:themes; oa:sdg:13 Climate action; oa:topic:T10029 Climate Change and Variability Research; oa:topic:T10330 Hydrological Modeling and Water Resource Management; oa:topic:T10466 Numerical Weather Prediction Models; openalex:import; openalex:yes

LSTM-based indoor air temperature prediction framework for HVAC systems in smart buildings - Mtibaa, Fatma; Nguyen, Kim-Khoa; Azam, Muhammad; Papachristou, Anastasios; Venne, Jean-Simon; Cheriet, Mohamed (Neural Computing and Applications, 2020)
Accurate indoor air temperature (IAT) predictions for heating, ventilation, and air conditioning (HVAC) systems are challenging, especially for multi-zone building and for different HVAC system types. Moreover, the nonlinearity of the buildings thermal dynamics makes the IAT prediction more difficult since it is affected by complex factors such as controlled and uncontrolled points, outside weather conditions and occupancy schedule. This paper presents a long short-term memory (LSTM) model to predict IAT for multi-zone building based on direct multi-step prediction with sequence-to-sequence approach. Two strategies, LSTM-MISO and LSTM-MIMO, are built for multi-input single-output and multi-input multi-output, respectively. The performance of these two strategies has been evaluated based on two case studies on real smart buildings using variable air volume (VAV) and constant air volume (CAV) systems. For both buildings, experimental results showed that the LSTM models outperform multilayer perceptron models by reducing the prediction error by 50%.
KerkoCite.ItemAlsoKnownAs: 10.1007/s00521-020-04926-3 5072953:SHT4N4QB 5072953:WQTUHTQI openalex: W3021449555
Keywords: CAV; HVAC; LSTM; Multi-step ahead predictions; Sequence-to-sequence; VAV; _important; _z:class:countries; _z:class:themes; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Autoregressive neural networks with exogenous variables for indoor temperature prediction in buildings - Delcroix, Benoit; Ny, Jérôme Le; Bernier, Michel; Azam, Muhammad; Qu, Bingrui; Venne, Jean-Simon (Building Simulation, 2021)
KerkoCite.ItemAlsoKnownAs: 5072953:EGDEINDB
Keywords: _important; _z:class:countries; _z:class:themes; selected_for:Predictive models for classroom conditions 2024; ⛔ No DOI found

LSTM-based indoor air temperature prediction framework for HVAC systems in smart buildings - Mtibaa, Fatma; Nguyen, Kim-Khoa; Azam, Muhammad; Papachristou, Anastasios; Venne, Jean-Simon; Cheriet, Mohamed (Neural Computing and Applications, 2020)
Accurate indoor air temperature (IAT) predictions for heating, ventilation, and air conditioning (HVAC) systems are challenging, especially for multi-zone building and for different HVAC system types. Moreover, the nonlinearity of the buildings thermal dynamics makes the IAT prediction more difficult since it is affected by complex factors such as controlled and uncontrolled points, outside weather conditions and occupancy schedule. This paper presents a long short-term memory (LSTM) model to predict IAT for multi-zone building based on direct multi-step prediction with sequence-to-sequence approach. Two strategies, LSTM-MISO and LSTM-MIMO, are built for multi-input single-output and multi-input multi-output, respectively. The performance of these two strategies has been evaluated based on two case studies on real smart buildings using variable air volume (VAV) and constant air volume (CAV) systems. For both buildings, experimental results showed that the LSTM models outperform multilayer perceptron models by reducing the prediction error by 50%.
KerkoCite.ItemAlsoKnownAs: 10.1007/s00521-020-04926-3 5072953:SHT4N4QB 5072953:WQTUHTQI openalex: W3021449555
Keywords: CAV; HVAC; LSTM; Multi-step ahead predictions; Sequence-to-sequence; VAV; _important; _z:class:countries; _z:class:themes; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:n:1; openalex:yes; selected_for:Predictive models for classroom conditions 2024

Gendered Impacts of Environmental Degradation in Informal Settlements: A Comparative Analysis and Policy Implications for India, Bangladesh, and Pakistan - Patel, Amit; Lotia, Hina; Malik, Ammar A.; Mundt, Marcia D.; Lee, Hyunjung; Rafiq, Muhammad Arshed (Journal of Comparative Policy Analysis: Research and Practice, 2020)
Degraded urban environments disproportionately affect marginalized populations, and especially impoverished women in South Asia’s informal settlements, where climate change vulnerabilities and gender inequalities are extreme. A comparative analysis was conducted of three neighboring countries, India, Bangladesh, and Pakistan, where urban environments, climate risks, and gender relations exhibit significant variances. With original survey data from 12 informal settlements across New Delhi, Dhaka, Islamabad, and Lahore, it was found that women are less empowered than men in all three countries, but their determinants related to environmental degradation and climate change vary. Qualitative data from key informants reveals several explanatory mechanisms of observed differences.
KerkoCite.ItemAlsoKnownAs: 5072953:CLQKCPFS 5072953:DFT6J8QC 5072953:LLYAF6N5
Keywords: _z:class:countries; comparative analysis; environmental degradation; informal settlements; mixed methods; women’s empowerment

Effects of ceiling fans on the thermal comfort of students in learning environments of Bayero University, Kano, Nigeria: 18th Windsor Conference - Ali, Sani Muhammad; Martinson, Brett; Al-Maiyah, Sura; Gaterell, Mark (Proceedings of the 10th Windsor Conference: Rethinking Comfort, 2018)
It is well known that thermal comfort is influenced by major physical parameters; air and radiant temperatures, humidity, and air speed in combination with personal attributes; clothing insulation and activity level. Although temperature is conventionally considered in adaptive thermal comfort model, as the most important physical parameter where cooling is involved, moderate air speed can enhance thermal comfort during higher temperatures. Through convective and evaporative cooling, ceiling fans cool people by causing sweat from the occupant’s body to evaporate. The northern part of Nigeria, being in the tropics, is known for higher temperature regimes for most part of the year. The use of air conditioning to achieve thermal comfort is not sustainable, for economic reasons and the lack of stable electrical energy. Therefore, a majority of naturally ventilated spaces could be kept thermally comfortable with the control of ceiling fans and operable windows. As part of a research work on learning environments in a Northern Nigerian university, this study reports on the effects of ceiling fans on the thermal comfort perception of the students in two lecture theatres. Air speed, air and radiant temperatures, relative humidity were measured, concurrently comfort surveys were undertaken inthe spaces, from which activity levels and clothing insulations were obtained. Adaptive thermal comfort standards, ASHRAE 55 and EN 15251, state that thermal comfort can be maintained as air temperature rises with the use of ceiling fans operating at moderate speed. The results show that reductions of 31% and 22% in overheating from the two lecture theatres were realised, as a result of ceiling fans usage, measured by the degree hour’s exceedance indicator. These results were further corroborated by the students’ acceptance of thermal conditions of the lecture theatres at temperatures above Tmax.
Keywords: Africa; Ceiling fans; overheating; thermal comfort; tropics

Retrofitting measures for climate resilience: Enhancing the solar performance of Malaysian school buildings with passive design concepts - Alwi, Najah Md; Flor, J-F; Anuar, Nur Hidayah Khairul; Mohamad, J; Hanafi, N N H; Muhammad, N H; Zain, M H K M; Nasir, M R M (IOP Conference Series: Earth and Environmental Science, 2022)
Climate-sensitive school buildings can enhance students’ learning performance and reduce the building’s overall energy consumption. This paper reports on a post-occupancy study of contemporary school buildings in Malaysia, assessing problems of solar heat gain. The research aims to propose retrofitting measures based on passive design principles adapted specifically for the Malaysian tropical climate to strengthen the resilience of local school buildings in a global climate emergency. On-site measurements in two different schools provided the empirical basis for the design modifications. The monitoring procedure included site observations, extended temperature and humidity measurements, and daylight analysis. A virtual classroom model was generated based on the on-site measurements, and a parametric simulation study was conducted to evaluate the proposed retrofit measures’ effectiveness. The model variables were evaluated and compared to identify the passive design elements that significantly impact heat gains and thermal comfort. The results showed that increasing roof overhangs to 1500 mm for additional shading, sensitive selection of roof materials and colours of white-painted zinc roof, and reduction of window-to-wall ratio by 30% to the operable windows helps to reduce solar gains by 6% to improve comfort conditions within the classrooms. Overall, the study provided evidence of how passive solar building design would benefit the climate resilience of Malaysian schools.
openalex: W4310789718
Keywords: C:Malaysia; _z:class:countries; _z:class:themes; evidence_review_2; oa:keyword:climate resilience; oa:keyword:malaysian school buildings; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:import; openalex:yes

Retrofitting measures for climate resilience: Enhancing the solar performance of Malaysian school buildings with passive design concepts - Alwi, Najah Md; Flor, J-F; Anuar, Nur Hidayah Khairul; Mohamad, J; Hanafi, N N H; Muhammad, N H; Zain, M H K M; Nasir, M R M (IOP Conference Series: Earth and Environmental Science, 2022)
Climate-sensitive school buildings can enhance students’ learning performance and reduce the building’s overall energy consumption. This paper reports on a post-occupancy study of contemporary school buildings in Malaysia, assessing problems of solar heat gain. The research aims to propose retrofitting measures based on passive design principles adapted specifically for the Malaysian tropical climate to strengthen the resilience of local school buildings in a global climate emergency. On-site measurements in two different schools provided the empirical basis for the design modifications. The monitoring procedure included site observations, extended temperature and humidity measurements, and daylight analysis. A virtual classroom model was generated based on the on-site measurements, and a parametric simulation study was conducted to evaluate the proposed retrofit measures’ effectiveness. The model variables were evaluated and compared to identify the passive design elements that significantly impact heat gains and thermal comfort. The results showed that increasing roof overhangs to 1500 mm for additional shading, sensitive selection of roof materials and colours of white-painted zinc roof, and reduction of window-to-wall ratio by 30% to the operable windows helps to reduce solar gains by 6% to improve comfort conditions within the classrooms. Overall, the study provided evidence of how passive solar building design would benefit the climate resilience of Malaysian schools.
openalex: W4310789718 KerkoCite.ItemAlsoKnownAs: 10.1088/1755-1315/1102/1/012014 2129771:BW22RJ67 4874017:97DE7AX9 5072953:AET5KVED
Keywords: C:Malaysia; _z:class:countries; _z:class:themes; evidence_review; oa:keyword:climate resilience; oa:keyword:malaysian school buildings; oa:sdg:13 Climate action; oa:topic:T10121 Building Energy Efficiency and Thermal Comfort Optimization; oa:topic:T10766 Urban Heat Islands and Mitigation Strategies; oa:topic:T11371 Urban Wind Environment and Air Quality Modeling; openalex:import; openalex:yes